2019
DOI: 10.1017/s1049096519001173
|View full text |Cite
|
Sign up to set email alerts
|

How Many Citations to Women Is “Enough”? Estimates of Gender Representation in Political Science

Abstract: Recent studies identified gendered citation gaps in political science journal articles, with male scholars being less likely to cite work by female scholars in comparison to their female peers. Although journal editors, editorial boards, and political scientists are becoming more aware of implicit biases and adopting strategies to remedy them, we know less about the proper baselines for citations in subfields and research areas of political science. Without information about how many women should be cited in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…Given that women constitute a clear critical mass in the politics and gender area, we expect female, male, and mixed gender authors to be similarly likely to cite work by women in Politics & Gender . Political methodology is the APSA section with the highest proportion of male members and thus we expect to confirm earlier analyses of Political Analysis , which show a clear gender gap in citations (Dion and Mitchell 2012). We anticipate that APSR will fall somewhere in the middle, given that it represents political science research broadly; 37.5% of APSA members self-identify as female (APSA 2017).…”
Section: Data and Analysessupporting
confidence: 77%
See 2 more Smart Citations
“…Given that women constitute a clear critical mass in the politics and gender area, we expect female, male, and mixed gender authors to be similarly likely to cite work by women in Politics & Gender . Political methodology is the APSA section with the highest proportion of male members and thus we expect to confirm earlier analyses of Political Analysis , which show a clear gender gap in citations (Dion and Mitchell 2012). We anticipate that APSR will fall somewhere in the middle, given that it represents political science research broadly; 37.5% of APSA members self-identify as female (APSA 2017).…”
Section: Data and Analysessupporting
confidence: 77%
“…We start with a basic question about gendered variance in citations: do women faculty receive fewer citations to their journal articles than male faculty? Several disciplines produce evidence of lower citation levels for female scholars compared to male scholars in the same field including economics (Ferber 1988; Ferber and Brün 2011), ecology (Cameron, White, and Gray 2016), political science (Dion and Mitchell 2012; Maliniak, Powers, and Walter 2013; Mitchell, Lange, and Brus 2013; Roberts, Stewart, and Nielsen 2017), library and information sciences (Håkanson 2005), linguistics and sociology (Leahey, Crockett, and Hunter 2008), and health and natural sciences (Aksnes et al. 2011; Beaudry and Larivière 2016).…”
Section: Research On Gendered Citation Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a case for citation rates being affected by ideological bias. This is particularly controversial at the present time in light of social justice calls for researchers to decolonize their reference lists, and include more women in their citations (Dion & Mitchell, 2020;Dworkin et al, 2020). However, in one high-profile example of ideological bias in citation rates, Honeycutt and Jussim (2020) found that studies of gender biases in academic hiring do not appear to be cited in accordance with ostensible scientific quality.…”
mentioning
confidence: 99%
“…2 These types of biases echo the enduring problems in political science. Gender gaps have been consistently identified in political science citations, syllabi, and books, whereas the academic study of politics historically has focused on a small number of wealthy countries (Dion and Mitchell 2019;Wilson and Knutsen 2020). The prominent initiatives Women Also Know Stuff and People of Color Also Know Stuff were motivated partly by a closely related bias: publications and events about politics are less likely to include experts who are white women or people of color (Beaulieu et al 2017;Lemi, Osorio, and Rush 2019).…”
mentioning
confidence: 99%